Identifying the markers and tagging a leucine-rich repeat receptor-like kinase gene for resistance to anthracnose disease in vegetable cowpea [Vigna unguiculata (L.) Walp.]. Issue 3 (4th May 2018) - Pradhan, Dolagobinda; Mathew, Deepu; Mathew, Sally K.; Nazeem, P. A.
ABSTRACT: Anthracnose caused by the fungus Colletotrichum lindemuthianum is the most destructive disease of cowpea. Field-type cowpeas show various levels of resistance, whereas pole-type vegetable cowpeas are highly susceptible. Transfer of resistance available in field types to vegetable types is a major breeding objective in cowpea. This paper details the development of an F2 mapping population by crossing field-type cowpea variety Kanakamony ( Vigna unguiculata ssp. cylindrica ) with pole-type vegetable cowpea variety Sharika ( Vigna unguiculata ssp. sesquipedalis ), screening this population with artificial inoculation and Bulked Segregant Analysis (BSA) with random marker systems Random Amplified Polymorphic DNA (RAPD) and Inter-Simple Sequence Repeats (ISSR); the objective is to identify the markers linked with major resistance-contributing genes. RAPD primer OPA02 has yielded marker at 850 bp in susceptible genome, whereas ISSR primers UBC810 and UBC811 have yielded markers at 1.4 kb and 1.5 kb respectively in resistant genomes. These markers were reproducible and their linkage with resistance and suitability in marker assisted selection (MAS) were confirmed through co-segregation analysis in F3 population. UBC811 marker was eluted, cloned on pGEM-T, and sequenced. The sequence had shown that this marker is anchored on LRR receptor-like serine/t\hreonine protein kinase gene which could be involved in the resistance mechanism.